RESEARCH OF MODELS FOR QUALITY ASSURANCE OF MULTISERVICE NETWORKS FUNCTIONING (Transport systems and technologies, 2018)
In this paper a methods of ensuring connection quality of telecommunication networks is considered. The analysis of the quality assurance mechanisms of the multiservicenetworks, and shows that they are linked to structural and organizational characteristics of the work. The models of functioning of network are researched and the estimation of parameters of quality of its work is conducted for the different size of the subscriber loading. In particular, the algorithm of calculating the delay time of the packet transmission network was made when using the quality assurance mechanisms integrated services and differentiated services, and comparison of their efficiency, depending on the number of network users. It is shown that the differentiated services model appears to be more flexible compared to integrated services because it provides less volumes of delay with large values of load.
Keywords: Multi-service network, Quality of Service, Integrated Services Model, Differentiated Services Model